Profitability and risk of European banks : a comparison between fixed and floating rates - Cordeiro, Ana Filipa Capela (2019)
The share of floating-rate loans and fixed-rate loans varies across countries and over time. This is a study about how the movements in monetary policy interest rates defined by the European Central Bank and the changes in the yield curve of the countries influence the share of floating-rate loans. Moreover, there is also an attempt to study the impact of this type of interest rate selection with the main components of profitability in banks. Using a ten-country panel and econometric models, I find that the monetary policy instruments do influence the choice of loans with variable rates. However, the effects of this choice on banks’ profitability is less significant, suggesting that it depends on other components. These conclusions contribute to the literature related with monetary policy and banks’ interest rate risk management.